Development and Validation of Modules in English 2: Writing in the Discipline - Emotin-Bucjan, Mardie D. (JPAIR Multidisciplinary Research, 2011)
Writing is one of the four macro-skills to be developed in language among the students. This paper focused on the Development and Validation of Modules in English 2: Writing in the Discipline. The modules aimed to enhance the basic organizational, judgmental and mechanical writing skills of students as they follow the writing process while performing written tasks and assignments required for their academic pursuits. The study utilized a content validated feedback questionnaire for the pool of experts, instructors and students. The study employed the descriptive method of research. The study underwent the four phases of material development namely: design phase, development phase, field-try out phase, and evaluation phase based on Johnson's Model (1998). The gathered data were statistically treated using the arithmetic mean and analysis of variance. The results of the study reveal that the contents; activities, exercises and techniques used in the modules were varied allowing the students to work independently and creatively; the over-all assessment of the pool of experts, teachers and students revealed that the modules were appropriate to the level and needs of the students; These conclusions were drawn: the varied activities and techniques used in the modules were very helpful to the learners, and the tandem of teaching and learning was evident allowing the students to work independently; the modules were very relevant and very useful for use in the class because these answer the need of the students to improve writing skill.
Keywords: Module Development; Writing in the Discipline; English 2; Validation Process; Academic Writing Skills